Exposure to selective serotonin reuptake inhibitors in utero and early elementary school outcomes. (25th February 2018) - Kragholm, K.; Andersen, M. P.; Mortensen, R. N.; Bech, L. F.; Polcwiartek, C.; Rohde, C.; Torp‐Pedersen, C.; Videbech, P.; Nielsen, J.
Abstract : Objective: Data on special education in offspring exposed to selective serotonin reuptake inhibitors (SSRIs) in utero are lacking. We examined associations of in utero SSRI exposure with special education needs and delayed elementary school start. Methods: A population‐based case‐cohort study using Danish nationwide birth and prescription registry data from 2005 to 2008. Follow‐up ends during 2011–2015 to capture special education needs during and delayed entry to the first elementary school year. Cases were in utero SSRI‐exposed offspring. Cohort‐controls were SSRI‐unexposed offspring of mothers previously on SSRIs. We reported odds ratios (ORs) and 95% confidence intervals (CIs), adjusted for relevant potential confounders. Results: Of 117 475 first‐incident non‐multiple pregnancy births, 3314 were SSRI‐exposed, and 3536 were unexposed. Among SSRI‐exposed offspring, 3.2% ( n = 98) had special school needs vs. 2.4% ( n = 77) in unexposed offspring, P ‐value=0.048. Correspondingly, 12.3% ( n = 383) among SSRI‐exposed children had delayed school entry vs. 9.4% ( n = 308) in unexposed offspring, P ‐value < 0.001. Adjusted OR for the association with special school needs was 1.12 (95% CI 0.82–1.55; P ‐value = 0.48) and 1.38 (95% CI 0.90–2.13; P ‐value = 0.14) for exposure in all three trimesters. The corresponding adjusted ORs for delayed school entry were 1.17 (95% CI 0.99–1.38; P ‐value = 0.073) and 1.40 (95% CI 1.11–1.76; P ‐value = 0.004). Conclusion: In utero SSRI exposure in all three trimesters was associated with delayed elementary school start but not special education needs.